Exploring consumer behavior and brand management in the automotive sector: Insights from a digital and territorial perspective - Diana Rodrigues; Bruno Sousa; Sofia Gomes; José Castro Oliveira; Eunice Lopes (Administrative Sciences, 2023)
Human beings are strongly influenced by their emotions; so, it is believed that building a close relationship between consumers and brands is a key factor for success. In this way, car brands are no exception, and despite facing numerous challenges associated with the energy transition, they have to reinvent themselves, retaining a focus on offering a unique and personalized experience for the consumer without forgetting the factors that influence the decision-making process. Therefore, current research aims to understand the relationship between brand love and other behavioral constructs, including brand attachment, brand satisfaction, brand loyalty, and positive word of mouth, as well as its influence on consumer behavior in the Portuguese automotive market, more specifically regarding the brands Audi, BMW, and Mercedes-Benz. Based on the literature review, a questionnaire survey was conducted on a group of 324 respondents. From this sample, it was possible to develop a conceptual model and formulate six research hypotheses. The results reveal that brand attachment and satisfaction have a positive influence on brand love, which has a positive influence on brand loyalty and positive word of mouth. In addition, brand attachment is positively related to brand loyalty, which has a positive impact on loyalty. Therefore, this article presents some insights from the perspective of digital marketing (i.e., e-WOM and social networks) and territory management (i.e., notoriety and positioning of territories). In the end, the limitations of the study will be presented, and guidelines for future research will be outlined.
Keywords: 350; automotive; brand love; consumer behavior; digital trends; territorial management